Lipase-catalyzed transesterification of (R,S)-1-phenylethanol in SC $CO_2$ and in SC $CO_2$/ionic liquid systems - Paljevac, Muzafera; Knez, Željko; Leitgeb, Maja (Slovensko kemijsko društvo, 2012)
Commercial immobilized lipase B from Candida antarctica (CALB) was successfully applied to catalyzing the transesterification of (R,S)-1-phenylethanol in supercritical carbon dioxide and in supercritical carbon dioxide/ionic liquid biphasic system. Firstly, the variables affecting the performance of CALB in transesterification reactions in supercritical carbon dioxide, such as CALB concentration, temperature and pressure, were studied. An increase in the conversion and in the reaction rate was observed as the CALB/substrate ratio, temperature and pressure, were increased from 4.3 to 19.9, from 40 °C to 80 °C and from 8 MPa to 10 MPa, respectively. Further increase in temperature from 80 °C to 120 °C and pressure from 10 MPa to 30 MPa resulted in lower conversion and lower initial reaction rate. Furthermore, different vinyl esters were used as acyl donors for CALB-catalyzed transesterification of (R,S)-1-phenylethanol in supercritical carbon dioxide. The highest initial reaction rate was attained with vinyl butyrate, although 50% conversion was attained faster when vinyl acetate was used as acyl donor. Secondly, in transesterification of (R,S)-1-phenylethanol, performed in supercritical carbon dioxide/ionic liquid biphasic system, influence of concentration of 1-butyl-3-methylimidazolium tetrafluoroborate [bmim][BF$_4$] was studied. The addition of 50 mmol (70% w/w reaction mixture) of [bmim][BF$_4$] to the reaction system gave the best result in terms of transesterification rate. Komercialno imobilizirano lipazo B iz Candida antarctica (CALB) smo uspešno uporabili kot biokatalizator za encimsko katalizirano transesterifikacijo (R,S)-1-feniletanola v SC $CO_2$ in v dvo-faznem sistemu SC $CO_2$/IL. Najprej smo proučili vpliv različnih reakcijskih parametrov, kot so razmerje CALB/substrati, temperatura in tlak, na aktivnost CALB v SC $CO_2$. Z naraščanjem razmerja CALB/substrati od 4.3 do 19.9, temperature od 40 °C do 80 °C in tlaka od 10 MPa do 30 MPa so naraščale presnove in začetne reakcijske hitrosti. Nadaljnje naraščanje temperature od 80 °C do 120 °C in tlaka od 20 MPa do 30 MPa je povzročilo znižanje tako presnove kot začetne reakcijske hitrosti. Nadalje smo za transesterifikacijo (R,S)-1-feniletanola v SC $CO_2$, katalizirano z imobilizirano CALB, uporabili kot donorje acilne skupine vinil estre z verigami različnih dolžin. Najvišjo začetno reakcijsko hitrost smo dosegli z vinil butiratom, čeprav smo 50% presnovo hitreje dosegli z vinil acetatom. V dvo-faznem sistemu SC $CO_2$/IL smo proučili vpliv koncentracije ionske tekočine 1-butil-3-metilimidazolijevega tetrafluoroborata [bmim][BF$_4$] na potek reakcije. Najvišjo začetno hitrost reakcije smo dosegli, ko smo reakcijo izvedli s 50 mmol (70% w/w reakcijske zmesi) [bmim][BF$_4$].